2021
DOI: 10.1177/00131644211033902
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Adaptive Measurement of Change to Item Parameter Estimation Error

Abstract: Adaptive measurement of change (AMC) is a psychometric method for measuring intra-individual change on one or more latent traits across testing occasions. Three hypothesis tests—a Z test, likelihood ratio test, and score ratio index—have demonstrated desirable statistical properties in this context, including low false positive rates and high true positive rates. However, the extant AMC research has assumed that the item parameter values in the simulated item banks were devoid of estimation error. This assumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Each simulation condition was replicated 1,000 times to represent 1,000 simulees for each combination of pattern, 𝜃 1 value, and CAT item bank. In addition, true (error-free) item parameters were used in the simulations because Cooperman et al (2021) showed that item parameter estimation error had a small to negligible effect on AMC performance in similar testing scenarios.…”
Section: Cat Administrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Each simulation condition was replicated 1,000 times to represent 1,000 simulees for each combination of pattern, 𝜃 1 value, and CAT item bank. In addition, true (error-free) item parameters were used in the simulations because Cooperman et al (2021) showed that item parameter estimation error had a small to negligible effect on AMC performance in similar testing scenarios.…”
Section: Cat Administrationmentioning
confidence: 99%
“…Their common practice was to specify a limited number of change patterns that represented different arbitrary combinations of magnitude, direction, and linear or nonlinear patterns of change. However, Cooperman et al (2021) showed that among design factors including hypothesis testing method, item parameter estimation error, starting 𝜃 value, and change pattern, the effect sizes of change pattern on most AMC performance indicators were far greater than other design factors. For example, in their results, the classical effect sizes ( 2 ) for true positive rates (TPRs, or power) were 0.793 for change pattern, 0.06 for starting 𝜃, and 0.049 for the change pattern × starting 𝜃 interaction.…”
mentioning
confidence: 92%
See 3 more Smart Citations